2016
DOI: 10.12659/msm.896225
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA-328 Functions as a Biomarker for Recurrence of Early Gastric Cancer (EGC) After Endoscopic Submucosal Dissection (ESD) by Modulating CD44

Abstract: BackgroundThis study investigated the molecular mechanism of the effect of CD44 on the recurrence of EGC after ESD, including the potential regulator and signaling pathways of CD44.Material/MethodsWe searched the miRNA online database (www.mirdb.org) with the “seed sequence” located within the 3′-UTR of the target gene, and performed luciferase assay to test the miRNA/mRNA relationship. We also determined the expression of CD44 in the EGC and control samples. In addition, statistical analysis was used to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…[2933]. This is similar to the result of Zhang et al [27], who studied the correlation between five miRNAs (miR-191, miR-28-3p, miR-145, miR-328, and miR-18a) in the serum of NSCLC patients and the three-year overall survival rate of the two groups. The result showed that miR-328 was differentially expressed in paired tumors and normal tissues ( P < 0.0001), that the target gene of miR-328 was mainly enriched in inflammatory/immune response pathways and pathways related to chemoradiotherapy and/or targeted treatment resistance, and that the miR-328 signal could play a role as a prognostic factor for patients with advanced NSCLC [29, 34].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[2933]. This is similar to the result of Zhang et al [27], who studied the correlation between five miRNAs (miR-191, miR-28-3p, miR-145, miR-328, and miR-18a) in the serum of NSCLC patients and the three-year overall survival rate of the two groups. The result showed that miR-328 was differentially expressed in paired tumors and normal tissues ( P < 0.0001), that the target gene of miR-328 was mainly enriched in inflammatory/immune response pathways and pathways related to chemoradiotherapy and/or targeted treatment resistance, and that the miR-328 signal could play a role as a prognostic factor for patients with advanced NSCLC [29, 34].…”
Section: Discussionsupporting
confidence: 82%
“…On the contrary, Xue et al discussed the role of miR-328 as a biomarker to predict tumor recurrence by studying the luciferase activity in the simulant of miR-328 with different concentrations. It was found that miR-328 could target CD44, and they showed a negative regulatory relationship between them, which indicated that detecting the expression level of miR-328 can be used as a means to predict the prognosis of gastric cancer patients [27]. miR-328 has been found to be associated with the prognosis of a variety of tumors in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CD44 also can be regulated by various molecules, signaling and some drugs. Some micro-RNAs have been found to negatively modulate CD44 expression, such as microRNA-150 [39], microRNA-200c [88], microRNA-34a [33], microRNA-330-5p [89], micro-RNA-145 [90], microRNA-3129 [91], microRNA-143 [92], microRNA-328 [93], and microRNA-373 [94]. CD44 has been reported to be a novel downstream target of microRNA-150 in nasopharyngeal carcinoma [39].…”
Section: Molecules and Pathways That Cd44 Regulatesmentioning
confidence: 99%
“…miR-200a-5p modulated PTEN, which recycles inositol-trisphosphate for the PIK3R3-AKT pathway ( Table 5). [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] IPA MicroRNA Target Filter. The five miRNAs were searched as a group with IPA MicroRNA Target Filter tool.…”
Section: Genomic Localization Of Mirnamentioning
confidence: 99%